Act Two. What Makes Popular Christian Music "Popular"?. A Comparison Between Current US-American Contemporary Christian Music and German Popular Christian Music Using the Examples of Lauren Daigle and Koenige & Priester Act Two. What Makes Popular Christian Music "Popular"? - Reinhard Kopanski (Journal for Religion, Film and Media, 2020)
The article discusses the question "What makes Popular Christian Music 'popular'?" by applying different (competing) concepts of the term "popular" so as to showcase by which criteria Popular Christian Music (labelled as Contemporary Christian Music by the US music industry) can be described as "popular". Thereby, the article compares both Anglo-American and German-language Christian songs by means of close reading using the examples of the German band Koenige & Priester [Kings & Priests] and US singer Lauren Daigle. Through the presented exemplary analyses, I argue that Christian music uses strategies of popularization comparable to secular popular music. The difference to secular music comes from the fact that the Christian message is a central genre marker of Popular Christian Music, leading me to suggest that the popularity (in the sense of reaching a large audience apart from religious/evangelistic circles) essentially depends on the polysemic properties of the lyrics.